Produção, qualidade nutricional e consumo do capim tanzânia por cabras mestiças sob manejo agroecológico no semiárido - Peixoto Junior, Gilvan Nogueira Alves (2014)
The objective of this study was to determine chemical composition, dry matter production of Tanzania grass pasture (Panicum maximum cv. Tanzania) in different periods of the year and estimate the consumption of crossbred goats using LIPE® as a marker under agroecological management. The experiment was conducted in Upanema-RN. The collection period was from May to November 2013. We used fifteen (15) adult goats permanently kept in the pasture. The grazing method used was fixed capacity and were evaluated 4 grazing periods. The animals in the paddock grazing period was two days, and the rest 30 days. The stocking rate was 2.44 AU per hectare. To determine the consumption were used eight (8) goats. The chemical composition of assessed pasture averaged: 19.1 to 22.4% for MS, 7.9 to 8.3 for PB, 64.2 to 65.8% for NDF and 38.5 to 40, 7% ADF. The forage accumulation varied from 2661.5 to 3548.6 kg DM / ha. The dry matter intake kg / day and% average live weight were 1.83 kg DM / day and 4.89% PV. The grass in Tanzania agroecologic irrigated, may be indicated for a dairy goat production systems, as presented DM yields and voluntary intake sufficient to meet the maintenance requirements of the animals. Despite the protein balance and energy have been a small negative supplementation would be enough for positive nutrient balance of animal production